INVESTIGATING SELF-REGULATED LEARNING HABITS OF DISTANCE EDUCATION STUDENTS - Kirmizi, Ozkan (Journal of History Culture and Art Research, 2013)
Abstract This study aims at exploring self-regulated learning habits of distance education students. Self-regulation can be defined as a process where learners take the initiative, with or without the guidance of others, in identifying their own needs, formulating goals, exploring resources, focusing on appropriate learning strategies, and evaluating learning outcomes. This study investigates self-regulated learning in terms of goal setting, environment structuring, time management, help seeking, self-evaluation, and metacognition. In the case of distance education learners, self-regulation assumes more importance due to the fact that distance education learners are supposed to direct their own learning process themselves. In order to collect data, Online Self-Regulated Learning Scale (OSLQ) and Motivated Strategies for Learning Questionnaire (MSLQ) were used. These two scales were adapted according to the scope of the study. The number of participants is 75. Results indicate that distance education learners must improve themselves in terms of their self-regulated learning habits.